Differential activation of spinal and parabrachial glial cells in a neuropathic pain model - Mussetto, Valeria; Moen, Aurora; Trofimova, Lidia; Sandkühler, Jürgen; Hogri, Roni (Frontiers in Cellular Neuroscience, 2023)
The clinical burden faced by chronic pain patients is compounded by affective comorbidities, such as depression and anxiety disorders. Emerging evidence suggests that reactive glial cells in the spinal cord dorsal horn play a key role in the chronification of pain, while supraspinal glia are important for psychological aspects of chronic pain. The lateral parabrachial nucleus (LPBN) in the brainstem is a key node in the ascending pain system, and is crucial for the emotional dimension of pain. Yet, whether astrocytes and microglia in the LPBN are activated during chronic pain is unknown. Here, we evaluated the occurrence of glial activation in the LPBN of male Sprague-Dawley rats 1, 4 and 7 weeks after inducing a chronic constriction injury (CCI) of the sciatic nerve, a prevalent neuropathic pain model. CCI animals developed mechanical and thermal hypersensitivity that persisted for at least 4 weeks, and was mostly reversed after 7 weeks. Using immunohistochemical staining and confocal imaging, we found that CCI caused a strong increase in the expression of the astrocytic marker GFAP and the microglial marker Iba1 in the ipsilateral spinal dorsal horn, with peak expression observed 1 week post-injury. Moreover, morphology analysis revealed changes in microglial phenotype, indicative of microglia activation. In contrast, CCI did not induce any detectable changes in either astrocytes or microglia in the LPBN, at any time point. Thus, our results indicate that while neuropathic pain induces a robust glial reaction in the spinal dorsal horn, it fails to activate glial cells in the LPBN.